Factors Affecting Employee Performance In Corona 19 Pandemic PT. Berlian Palugada Perkasa CilegonBanten - Suhartini Suhartini (Primanomics : Jurnal Ekonomi & Bisnis, 2021)
The pandemic period which lasted throughout 2020 gave its own meaning to a company, this study aims to determine the factors- factors affecting employee performance during the pandemic corona 19 at PT Berlian Palugada Perkasa Cilegon Banten. This study used a sample of 50 employees of PT. Berlian Palu Gada Cilegon, which is a saturated sample. The method is descriptive quantitative method and the analysis used includes reliability testing, validity testing, classical assumption tests, multiple linear regression analysis and hypothesis testing with the help of SPSS software version 25.0. Based on the results of the study, it shows that partially the work experience variable has a significant effect on employee performance by 4.005 with a significance of 0.000, so partially the work ability variable has a significant effect on employee performance by 2.533 with a significance of 0.015 and together the work experience and work ability variables have a significant effect. on employee performance of 27.042 with a significance of 0.000. However, management still needs to pay attention to indicators in work experience and ability, especially by providing training and development for employees so that the expected performance is in accordance with the organization's goals.